2004
DOI: 10.1016/j.buildenv.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil moisture transfer on building heat loss via the ground

Abstract: In this paper, the influence of soil moisture transfer on building heat loss via the ground is investigated by comparing fully coupled simulations with linear thermal simulations. The observed influences of coupling are (1) the larger amplitude of surface temperature, (2) the variation of thermal conductivity with moisture content, and (3) the advection of sensible heat by liquid transfer. In a parameter study, it is shown that these conclusions hold for a variety of climates, soils and foundation construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…Soil thermal conductivity and capacity highly rely on soil moisture and movement of soil water leads to thermal storage or transfer [42]. In addition, evaporation normally plays a crucial role in surface heat balance of dry area.…”
Section: Discussionmentioning
confidence: 99%
“…Soil thermal conductivity and capacity highly rely on soil moisture and movement of soil water leads to thermal storage or transfer [42]. In addition, evaporation normally plays a crucial role in surface heat balance of dry area.…”
Section: Discussionmentioning
confidence: 99%
“…A computational approach for heat transfer through the ground has been well defined (EN ISO 13370:2007, and simplified methods have been developed (Staszczuk, Radon, and Holm 2010). However, these approaches generally ignore the transfer of soil moisture, which is not negligible (Janssen, Carmeliet, and Hens 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Different models exist for the calculation of sky temperatures: a comparison in [24] indicated that the deviations are not that large. The model presented in this paper applies: (16) A model relating the cloudiness cf to the short-wave radiation was presented by Kasten and Czeplak [26], but was shown to give erroneous results in [24]. The cloudiness factors are thus adopted from solar radiation measurements [27], which though only allow deriving a year-averaged value.…”
Section: Heat and Moisture Transfer Inside Building Componentsmentioning
confidence: 99%
“…Ground surface temperature is taken equal to the air temperature, based on [24,25]. Different models exist for the calculation of sky temperatures: a comparison in [24] indicated that the deviations are not that large. The model presented in this paper applies: (16) A model relating the cloudiness cf to the short-wave radiation was presented by Kasten and Czeplak [26], but was shown to give erroneous results in [24].…”
Section: Heat and Moisture Transfer Inside Building Componentsmentioning
confidence: 99%